The Chinese Challenge to the American Strategy in the Middle East after 2001 AD - Salih, Alan H.S.; Hasan, Kamal A. Hasan (Mitanni Journal of Humanitarian Sciences, 2023)
Abstract China's new policy towards Central Asia, after the former Soviet Union, has been in a deep understanding that this region has painted a new geopolitical map. Because of the economic, political, and only economic alleys of this area for China, it has increased in importance, especially as there is a prolongation in terms of Chinese development in that area to the Region (Singh Yang) . One of the most important reasons for China's importance to Central Asia can be summarized in: A- China's fear of having a national, religious, and working force on the Singh Yang region, known as Eastern Turkistan, most of the population is Muslim In 2003, Beijing talked about the activation of five islamic political separatist groups in the region, a clear sign of China's anxiety in the region. Apart from that, China has more than 7,500 kilometers of border with them. B- Central Asia is a energy source from china's point of view, which is a major necessity after the economic development of one after the one that sees itself, this development of China in 1993 led China to import oil. We understand very well that when we know what we are doing against the increase in local production by 1%, China needs to use more energy by 0.528%. T- China is trying to connect the economics of this area to china's economics China is very strong by limiting the role of America and Europe in this area Despite the fact that China is trying to expand its relations with this region, sometimes it relies on Russia to achieve this expansion and sometimes And the other one is trying independently, China has tried to have an operation in this area through the establishment of shanghai organization to help We don't mention that Russia doesn't help China in entering this area in a way, because Russia understands the importance and ability of China that it can in a short time the central Asian market control with food and use China currently has high-level economic development in the world, despite its strategic weight at the regional and international levels and the existence of military institutions and high-level modernism alongside a rich cultural and historical background, all of which have made it a position and To play an important role and place in the international community and to be of importance to researchers and thinkers in intellectual institutions and research centres, one of the most important considerations that are being analyzed today is capable of and China's international and regional power and position of China's role and strategy in Central Asia.